Norms and Their Violation: From Scientific to Lay Thinking. An Exploratory Study from a Sample of Young Russian Adults - Sachkova M.Ye.; Berezina E.B.; Dvoryanchikov N.V.; Bovina I.B. (Культурно-историческая психология, 2021)
Problem. The problem of norms and norms violation has a long research history in scientific thinking. Lay thinking analysis rests in the shadow of this research line; although in the modern world people are actively involved in the construction of lay theories about various phenomena and they use this knowledge in daily life. Aim. Following the ideas of the social representations theory, the aim of the exploratory study was to analyse the lay theories developed by young Russian adults about norms and norms violation. Method. 134 young adults participated in the study, 26.12% males (aged 18 — 28 years, M=21.01years, SD =2.23). 71.6% participants were students of social sciences from Moscow Universities. A free-association technique was used. The data were analysed by using prototypical analysis. Results. The particularity of lay thinking about norms and norms violation was revealed. Conclusion: It is possible to conclude that norms are not equated with laws, while norms violation is identified with crimes (laws’ violation). The framework of the social representations theory allowed us to analyse the lay thinking about norms and norms violation as a matter of Russian cultural context.